2020
DOI: 10.3389/fgene.2020.529757
|View full text |Cite
|
Sign up to set email alerts
|

miR-149-5p Regulates Goat Hair Follicle Stem Cell Proliferation and Apoptosis by Targeting the CMTM3/AR Axis During Superior-Quality Brush Hair Formation

Abstract: The Yangtze River Delta white goat is a unique goat species that can produce superior quality brush hair. CKLF-like MARVEL transmembrane domain-containing 3 (CMTM3), which influences the transcriptional activity of androgen receptor (AR), was identified as a candidate gene related to superior-quality brush hair formation. CMTM3 is generally expressed at low levels, but miR-149-5p is highly expressed in the skin tissues of these goats. The mechanism by which CMTM3 regulates the proliferation and apoptosis of go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…RegRNA 2.0 (http://regrna2.mbc.nctu.edu.tw/index.html) and RNAhybrid (v2.1.2) software were used to obtain the secondary structure and information on the binding sites between circCOL1A1 and miR-149-5p. The miR-149-5p/ CMTM3/AR axis was constructed and identified in our previous study (Wang et al, 2020). Sanger sequencing, PCR with divergent and convergent primers, RNase R treatment, actinomycin D treatment, and cytoplasmic and nuclear RNA purification assays were used to identify the structure and specificity of circCOL1A1.…”
Section: Circrna Selection and Specificity Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…RegRNA 2.0 (http://regrna2.mbc.nctu.edu.tw/index.html) and RNAhybrid (v2.1.2) software were used to obtain the secondary structure and information on the binding sites between circCOL1A1 and miR-149-5p. The miR-149-5p/ CMTM3/AR axis was constructed and identified in our previous study (Wang et al, 2020). Sanger sequencing, PCR with divergent and convergent primers, RNase R treatment, actinomycin D treatment, and cytoplasmic and nuclear RNA purification assays were used to identify the structure and specificity of circCOL1A1.…”
Section: Circrna Selection and Specificity Identificationmentioning
confidence: 99%
“…4) CMTM3 was confirmed as a target gene of miR-149-5p, and during superiorquality brush hair formation, miR-149-5p could regulate hair follicle stem cell proliferation and apoptosis by targeting the CMTM3/AR axis (Wang et al, 2020). 5) CMTM3 knockdown accelerates hair follicle stem cell proliferation and promotes AR expression, while overexpression of CMTM3 significantly inhibits the proliferation of stem cells and is accompanied by a reduction in the AR expression level (Wang et al, 2020;Wang et al, 2021). This critical evidence suggests that a series of protein-coding genes and noncoding RNAs (ncRNAs) are important for the formation of superior-quality brush hair.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most important, caspases and Bcl-2 may be targets that regulate the apoptosis for HFSCs. For example, the Jian group revealed that a miR-149-5p inhibitor can suppress the proliferation and trigger the apoptosis of HFSCs, while miR-149-5p can upregulate the expression of Bcl-2 and downregulate caspase 3, as well as induce anti-apoptotic responses during superior-quality brush hair formation [ 170 ].…”
Section: Signals and Signaling Pathways In Hfscsmentioning
confidence: 99%
“…Functional studies indicated miR-149-5p plays an important role in the formation of high-quality hair traits. Through the post-transcriptional mechanism, it can inhibit the expression of CKLF-like MARVEL transmembrane domain-containing 3 (CMTM3), promote the proliferation of goat hair follicle stem cells and inhibit the apoptosis of hair follicle stem cells (33).…”
Section: Other Functionsmentioning
confidence: 99%